2011
DOI: 10.2134/agronj2011.0162
|View full text |Cite
|
Sign up to set email alerts
|

Soil Salinity and Quality of Sprinkler and Drip Irrigated Cool‐Season Turfgrasses

Abstract: A 3‐yr study was conducted in New Mexico to investigate the effects of saline water on changes in quality, cover, and root zone salinity of seven cool‐season turfgrasses. Plots were irrigated using either sprinklers or subsurface drip with water of 0.6, 2.0, or 3.5 dS m−1. From March to November plots were rated monthly for quality, and green cover was determined using digital image analysis. Soil samples were collected at depths of 0 to 10, 10 to 20, and 50 to 60 cm in June and November and analyzed for elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 26 publications
6
29
0
Order By: Relevance
“…Salinity was also not problematic when saline water was applied through SDI. Although our results confirm those of Sevostianova et al (2011a) and Schiavon et al (2012Schiavon et al ( , 2013, who documented increased salinity levels in soil irrigated through SDI, quality and NDVI of subsurface-irrigated turf did not differ for two of the 3 yr between those given saline water and those receiving potable water. These results suggest that it is possible to maintain acceptable quality in warm-season species in an arid environment with deficit irrigation (50% ET OS ) and saline water.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Salinity was also not problematic when saline water was applied through SDI. Although our results confirm those of Sevostianova et al (2011a) and Schiavon et al (2012Schiavon et al ( , 2013, who documented increased salinity levels in soil irrigated through SDI, quality and NDVI of subsurface-irrigated turf did not differ for two of the 3 yr between those given saline water and those receiving potable water. These results suggest that it is possible to maintain acceptable quality in warm-season species in an arid environment with deficit irrigation (50% ET OS ) and saline water.…”
Section: Discussionsupporting
confidence: 65%
“…Beard (1973) predicted limited or no success for subsurface irrigation on turf. Findings by Sevostianova et al (2011a) confirmed some of these concerns and suggested that sprinklers are more efficient than subsurface drip lines in leaching salt from the root zone.…”
Section: 1mentioning
confidence: 80%
See 1 more Smart Citation
“…Several studies have shown that quality of turf does not decrease over time when irrigated with potable water from a subsurface drip irrigation system (Moore, 2006;Schiavon et al, 2010Schiavon et al, , 2011Sevostianova et al, 2011aSevostianova et al, , 2011b. However, there may be limitations in the ability of SDI systems to leach salts from the root zone.…”
mentioning
confidence: 99%
“…However, there may be limitations in the ability of SDI systems to leach salts from the root zone. When SDI systems in combination with saline water are used to irrigate turf areas the fraction of the root zone above the emitters (where most of the roots are accumulated) that receives water only through capillary raise may not be sufficiently flushed with water to leach out the salts (Schiavon et al, 2013;Sevostianova et al, 2011aSevostianova et al, , 2011b.…”
mentioning
confidence: 99%